THE DEVELOPMENT OF LIBRARY CATALOG: FROM PAPER TO ELECTRONIC - Mukhtaruddin; Asnawi; Eliza Rahmi (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Humaniora Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The development in information and communication technologi has changed the way of users in accessing the information in libraries. The libraries have replaced their card catalogues to OPACs and WebPACs. This research employs a descriptive qualitative approach through a literature review. This paper defines the concept of OPACs and WebPACs, confers the development of OPACs & WebPACs technology in libraries, explaines the distinction between OPACs and Card Catalogues, and explains various features and advantanges of WebPACs.